Pengaruh Kompetensi dan Kepemimpinan terhadap Kinerja Pegawai dengan Komitmen Organisasi sebagai Variabel Intervening - Firdian Wahyuni (Universitas Putra Indonesia YPTK Padang, 2022)
This study aims to determine the effect of competence and leadership on employee performance with organizational commitment as an intervening variable in the Sub-District of Sawahlunto City. The method used is multiple linear regression analysis and path analysis. by distributing a questionnaire of 130 respondents. The results obtained that there is a positive and significant influence of competence on organizational commitment in the Sub-District of Sawahlunto City. There is a positive and significant influence of leadership on organizational commitment in the Sub-District of Sawahlunto City. There is a positive and significant effect of competence on employee performance in the Sub-District of Sawahlunto City. There is a positive and significant influence of leadership on employee performance in the Sub-District of Sawahlunto City. There is a positive and significant effect of organizational commitment on employee performance in the Sub-District of Sawahlunto City. Organizational commitment mediates the effect of competence on employee performance in the Sub-District of Sawahlunto City. Organizational commitment mediates the influence of leadership on employee performance in the Sub-District of Sawahlunto City. Finally, the authors suggest to the Sub-District of Sawahlunto City to further increase organizational commitment, competence and leadership so that employee performance is expected to increase.